The best of Dagmay, 2007 to 2009 - De Ungria, Ricardo M.; Tiu, Macario D.; Cruz, Jhoanna Lynn B.; Cimafranca, Dominique Gerald M. (Tubao Book series of the Davao Writers Guild, 2010)
A collection of fiction, poetry, drama, and creative nonfiction from more than 200 young Davaoeño and Mindanaoan authors.